Telemedicine Solution for Multidisciplinary Care Delivery: A User Requirements Analysis. (September 2022) - Elsiss, Farah; Chun, Nathan; Keyser, Colette; Park, GeeBeum; Winn, Mckensie; Ammar, Dania; Bao, Shan
The main goal of this paper is to apply a user-centered approach to develop a telemedicine solution, Medlly, to support multidisciplinary care delivery. For this purpose, three key tasks for the proper conduction of the remote visit between the various medical specialists and the patient were considered: (1) the scheduling procedure, (2) the online communication meeting, and (3) the conglomerate after-visit summary. The goal was achieved through the application of user requirements analysis methods including task analysis, prototyping, and usability testing which was conducted with actual healthcare providers. Results showed that the developed multidisciplinary telemedicine prototype ensures efficient interaction between the interface and its users.